The Financial Crisis and the Global Shadow Banking System - Maryse Farhi; Marcos Antonio Macedo Cintra (Revue de la Régulation)
The financial crisis triggered by increasing default rate, real estate devaluation and financial asset depreciation associated with the US subprime mortgages brought back the debate about the framework of the US and international financial systems, their potential systemic risks, and their regulatory and supervisory mechanisms. Credit derivatives and structured products backed by real estate credit replicated and multiplied risks by an unknown factor besides redistributing them at a global scale. A large number of poorly regulated and badly supervised financial institutions – no capital requirements, no access to deposit insurances, rediscount operations, and last resort credit lines by central banks – became the counterparty of the credit risk transfer from the banking system and started to hold increasing risks. The intermingling of these institutions and markets engendered a global shadow banking systems and markets.